Switched Control Based on Takagi-Sugeno Fuzzy Model for Dual Active Bridge DC-DC Converter - Oncoy, Dante J. S. [UNESP]; Cardim, Rodrigo [UNESP]; Teixeira, Marcelo C M [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
The use of the Dual Active Bridge (DAB) DC-DC converter has been increasing in recent years in several applications. This paper proposes the application of a nonlinear control strategy for the DAB converter, which consists of switching linear controllers based on a switching function. In order to achieve this, the Takagi-Sugeno (T-S) fuzzy model of the DAB converter is realised as a convex combination of linear systems considering the load of the converter as an uncertain parameter. The switching function is chosen based on the uncertain parameters of the (T-S) fuzzy model and linear controllers are designed using some theorems based on Lyapunov stability theory with the use of Linear Matrix Inequalities (LMI's). The results of the control strategy are validated by simulation, verifying an improvement in the dynamic response and robustness against parameter variations with respect to the linear controllers widely used in the DAB converter.
Keywords: Dual Active Bridge (DAB); Linear matrix inequalities (LMI's); Switched control; Takagi-Sugeno (T-S) fuzzy Model